2003
DOI: 10.1111/j.1752-0606.2003.tb01691.x
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐family Psychoeducation Groups in the Treatment of Children With Mood Disorders

Abstract: This study examined the impact of adjunctive multi-family psychoeducation groups (MFPG) on mood-disordered children aged 8 to 11 and their families. Participants were 35 children and 47 parents from families randomly assigned to either immediate MFPG plus treatment as usual (n = 18) or a 6-month wait-list condition plus treatment as usual (n = 17). At the 6 month follow up, immediate treatment families reported: Increased parental knowledge about childhood mood symptoms; increased positive family interactions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
80
1
7

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 125 publications
(89 citation statements)
references
References 36 publications
1
80
1
7
Order By: Relevance
“…Previous research provides support for the efficacy of adjunctive family-focused psychoeducation and skills-based interventions for youth with BPSD, including psychoeducational psychotherapy (PEP), family-focused treatment, and child-and family-focused cognitive behavioral therapy West et al 2014). PEP has the strongest evidence base for treating children £12 years of age with BPSD (Fristad et al 2002(Fristad et al , 2003Fristad 2006;Fristad et al 2009;Mendenhall et al 2009;Fristad and MacPherson 2014). Key goals of PEP are to provide psychoeducation about mood disorders and treatments, provide social support, and build skills in symptom management, emotion regulation, problem solving and communication.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research provides support for the efficacy of adjunctive family-focused psychoeducation and skills-based interventions for youth with BPSD, including psychoeducational psychotherapy (PEP), family-focused treatment, and child-and family-focused cognitive behavioral therapy West et al 2014). PEP has the strongest evidence base for treating children £12 years of age with BPSD (Fristad et al 2002(Fristad et al , 2003Fristad 2006;Fristad et al 2009;Mendenhall et al 2009;Fristad and MacPherson 2014). Key goals of PEP are to provide psychoeducation about mood disorders and treatments, provide social support, and build skills in symptom management, emotion regulation, problem solving and communication.…”
Section: Introductionmentioning
confidence: 99%
“…Key goals of PEP are to provide psychoeducation about mood disorders and treatments, provide social support, and build skills in symptom management, emotion regulation, problem solving and communication. Fristad and colleagues have developed a PEP manual (Fristad et al 2011c) and completed three previous randomized controlled trials (RCTs) (Fristad et al 2002(Fristad et al , 2003Fristad 2006;Fristad et al 2009;Mendenhall et al 2009) and an effectiveness trial ). These trials have demonstrated PEP's efficacy in improving mood symptoms, family interactions, parent understanding of mood disorders, access to quality mental healthcare, and high degrees of treatment satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…Danielson et al (2004) are testing a 12-session cognitive-behavioral therapy (CBT) for BP adolescents. For preadolescent BP, Fristad et al (2003) tested the efficacy of a multifamily psychoeducational group. As compared with a waitlist control condition, parents receiving multifamily psychoeducational group therapy were more knowledgeable about their child's mood disorder and more successful obtaining health services for their child over 6-month follow-up.…”
mentioning
confidence: 99%
“…In bipolar disorder, family, couple, and parent psychoeducation programs also have significantly improved nonverbal interactions, caregiver knowledge of the disorder, patient understanding of the illness, positive family interactions, caregiver distress, coping, attributions, patient functioning, and patient medication adherence (Bland & Harrison, 2000;Brent, Poling, McKain, & Baugher, 1993;Clarkin, Carpenter, Hull, Wilner, & Glick, 1998;Fristad, Goldberg-Arnold, & Gavazzi, 2003;Simoneau, Miklowitz, Richards, Saleem, & George, 1999;van Gent & Zwart, 1991).…”
mentioning
confidence: 99%